Brief review of the monograph assessment of long-term runoff in the southwestern part of the African continent (scenarios of long-term changes in probability characteristics) - Peter Buharitsin; Modest Kuame Kuasi (Annals of Marine Science - Peertechz Publications, 2024)
For the physical and geographical conditions of the African continent, it is more acceptable to simplify the runoff formation model by adapting to the relatively poorly studied long-term river flow regime of North Africa. The solution to the problems is based on the methodology of partially infinite modeling, developed in Russia and used in countries of Latin America and Africa with hot climates.